Model Pengembangan Pelukis Mandiri dengan Pengembangan Industri Kreatif - Fanni Husnul Hanifa (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2013)
In the industrial companies, the most important thingis theproduct sales marketing strategy both large and small companies. How consumers couldbuy products from the company if the marketing system still not running properly. IncludingThe Community Unit Activities should also have a product marketing strategy, so that the products which was  produced could be known and will attract the consumers. In this case we want to raise a quite famous The Community Unit Activities for it’s art specially in paintings from Desa Jelekong. Providing training in marketing strategy for paintings produced by an artists so it will be knownby the public, especially for fans or collector of paintings. Painter scan sell their paintings based on right marketing strategy. Besides promoting its painting, they can also developing other business opportunities. With training, we are hoping painters more independent, develop culture of entrepreneurship among the painters and improvement the quality of its product.